Existence and uniqueness of solutions for nonlinear hyperbolic fractional differential equation with integral boundary conditions - Tellab, Brahim; Haouam, Kamel (International Journal of Applied Mathematical Research, 2016)
In this paper, we investigate the existence and uniqueness of solutions for second order nonlinear fractional differential equation with integral boundary conditions. Our result is an application of the Banach contraction principle and the Krasnoselskii fixed point theorem.